Therapeutic potential of Chromolaena odorata, Vernonia amygdalina, and Cymbopogon citratus against pathogenic Bacteria - Udensi Justina Ugochi; Anyanwu Charles Obinna; Emedoh Andrew Emeka; Anyanwu Emilia Oluchi; Danladi Makeri; Pius Theophilus; Ezera Agwu (Scientific Reports)
Abstract Antimicrobial resistance poses a global public health threat, compelling the search for alternative treatments, especially in resource-limited settings. The increasing ineffectiveness of traditional antibiotics has intensified the need to explore medicinal plants as viable therapeutic options. This study sought to compare the efficacy of certain medicinal plants used in Owerri, Nigeria, for treating pathogenic bacteria against traditional commercial antibiotics. We tested graded concentrations (25 mg/ml, 50 mg/ml, 75 mg/ml, and 100 mg/ml) of ethanolic extracts of Awolowo leaf (Chromolaena odorata), Bitter leaf (Vernonia amygdalina), and Lemon grass leaf (Cymbopogon citratus) against Salmonella spp, Klebsiella spp, Escherichia coli, and Staphylococcus aureus employing the agar well diffusion method to measure zones of inhibition. Commercial antibiotics studied included: Pefloxacin, Gentamycin, Ampiclox, Zinnacef, Amoxicillin, Rocephin, Ciprofloxacin, Streptomycin, Septrin and Erythromycin, Sparfloxacin Amoxicillin, Augmentin, and Tarivid. Each experiment was conducted in triplicate to ensure accuracy and reproducibility. Results were analyzed descriptively and presented as mean zones of inhibition and standard deviations. One to three plant species exhibited antibacterial activities (zones of inhibition) across 25–100 mg/ml concentrations. In contrast, some or all antibiotics only exhibited antibacterial activities at 100 mg/ml concentration (none at 25–75 mg/ml concentrations). Zones of inhibition (10.3–14.1 mm) of all three plant species against E.coli and Klebsiella at 100 mg/ml concentration were higher than those of 8–10 antibiotics. C. odorata had shown high zones of inhibition of 11.8 and 11.0 mm against Salmonella spp. and S. aureus at 100 mg/ml concentration, which were higher than those of eight antibiotics. The other two plant species (C. citratus and V. amygdalina) had exhibited low zones of inhibition against Salmonella spp. and S. aureus, which were higher than those of 3 or 4 antibiotics at 100 mg/ml concentration. In general, the antibacterial activities of the three plant species across 25–100 mg/ml concentrations were higher than those of many antibiotics. To a large extent, the efficacy of medicinal plant extracts across different concentrations against bacterial strains was higher than that of many antibiotics. Those plant species have therefore shown some potential to be used as alternative or complementary therapeutics to antibiotics in addressing antibiotic resistance. Since the promising findings were based on an in vitro study, we recommend clinical trials to establish safe and effective doses of those plant extracts in humans.